Secondary hyperparathyroidity in patients with progressive chronic kidney disease - Dinh, Thi Minh Hao; Vo, Tam (Tạp chí Y Dược Huế, 2024)
In patients with end-stage chronic kidney failure, there are a number of disorders that cause bone damage. In particular, secondary hyperparathyroidism (SHPT) is related to chronic kidney failure, a calcium-phosphorus metabolism disorder that causes bone disorder. Secondary HPT occurs when parathyroid hormone(PTH) is continuously produced in response to chronically low serum calcium levels, commonly seen in patients with progressive chronic kidney disease. In this article we present a case of secondary HPT causing facial and thoracic bone changes